The beginning of the «church revolution»: Ekaterinoslav diocesan Congress of the clergy and the laity March 21–22, 1917 - Savchenko, S. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Abstract Introduction. Church Revolution of1917 in provincial dioceses have not studied the problem. Revolution Church is part of the political revolution, but it has received little attention in historiography. Ekaterinoslav diocese was one of the largest in the European part of the Russian Empire. Its reaction to the February 1917 revolution is almost unexplored because of the lack of archival sources in the local archive. Purpose. We aim to reconstruct the first reaction of the diocese clergy and parishioners to the revolutionary events in the state. To this end, we plan to rely on sources that have not been used by researchers. Results. Position of the Ekaterynoslav clergy was revolutionary and renovationism (obnovlenchestvo). In March local clergy not protested against the revolution. Bishop Agapit not fought with revolutionary clergy and laity and blessed diocesan meeting. The confrontation between the Bishop and Diocesan Committee in March has not been very noticeable. Originality. The revolution was perceived positively by the Ekaterinoslav clergy. This fact was founded on the numerous diocese documents. Ukrainian question in the first diocesan convention was not considered. Requirements clergy were mostly utilitarian and focused on the redistribution of financial resources and authority in the diocese. Requirements of the laity had not political or national character. Parishes want to organize the liturgy order, people's morality and clergy mode of life. Conclusion. The topic is not complete and requires additional study. The documents of central and regional archives and the archives of the Holy Synod will fully investigate. The task of further research is the reconstruction of the church and social events throughout the Ekaterinoslav diocese in the 1917.